Suppressing morphology-dependent resonances in laser-induced fluorescence signals of fuel droplets using a two-dye approach - Koegl, Matthias; Glahn, Jake; Zigan, Lars (Applied Optics, 2025)
The present study focuses on suppressing morphology-dependent resonances (MDRs) in laser-induced fluorescence signals of micrometric fuel droplets. The fluorescence signal is generated by doping the fuels with the fluorophore nile red and its excitation by a pulsed Nd:YAG laser at 532 nm. The fluorescence signals are collected by a spectrometer and an imaging setup. In general, the MDRs appear at longer wavelengths in the emission spectrum compared to the fluorescence maximum. These artefacts can lead to large measurement uncertainties, especially for ratio-based fluorescence techniques. An admixture of the second dye solvent blue 38 (S38), which shows an absorption band matching the MDR emission of nile red, enables a suppression of MDRs that are also shifted to larger wavelengths. The study investigates the influence of S38 at various concentrations to the fluorescence signal of nile red in micrometric spherical ethanol droplets between 40 µm and 80 µm. Furthermore, the investigations revealed that an increase in laser fluence inevitably requires a larger concentration of S38. A sufficient admixture of S38 for a certain concentration of nile red ensures a full suppression of the MDRs in nile red fluorescence signals and facilitates reliable measurement conditions for droplet studies.
CRIS-Team Scopus Importer:2025-02-14